The Effect of Neem, Citronella, Castor Oil, and Their Mixtures against Crocidolomia pavonana F. (Lepidoptera: Crambidae) - Leni Maryani; Danar Dono; Endah Yulia (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2019)
Cabbage-heart caterpillar, Crocidolomia pavonana F. (Lepidoptera: Crambidae), is one of the important pests in Brassicaceae family. Alternative control for cabbage-heart caterpillar that can be used is insecticide made from plant extracts. Neem, cirtonella and jatropha oil are reported to have an insecticidal properties. This study aimed to determine the effect of singgle or combination of neem, citronella, and castor oil to against C. pavonana larvae and to obtain the most effective ratio and concentration of oil combinations. The experimental method used in this research was Randomized Block Design with 41 treatments, i.e. control, single neem, citronella, castor oil and its combination each tested at concentration of 1%; 0,5%; 0,25%; and 0,1%. Each treatment was replicated 3 times. The results of this experiment showed that single oil or combination of neem, citronella and castor oil at consentration of 1% and 0,5% caused 100% larvae mortality, 1:3:2 ratio at 1% concentration was able to reduce food consumption, 3:2:1 ratio at 0,25% concentration was inhibit larvae development and reduce the weight of pupae, and 3:1:2 ratio at 0,5% concentration can reduce the weight of larvae.